Accomplices of the Hypoxic Tumor Microenvironment Compromising Antitumor Immunity: Adenosine, Lactate, Acidosis, Vascular Endothelial Growth Factor, Potassium Ions, and Phosphatidylserine - Vaupel, Peter; Multhoff, Gabriele (Frontiers in Immunology, 2017)
In this minireview, we aim to highlight key factors of the tumor microenvironment including adenosine (ADO), lactate, acidosis, vascular endothelial growth factor (VEGF), extracellular potassium ions, phosphatidylserine (PS) and tumor hypoxia with respect to antitumor immune functions. Most solid tumors have an immature chaotic microvasculature that results in tumor hypoxia. Hypoxia is a key determinant of tumor aggressiveness and therapy resistance and hypoxia-related gene products can thwart antitumor immune responses.